Critical Thinking and Learning Interest in Academic Achievement: The Mediating Role of ChatGPT - Wahyu Indriyani; Harsono Harsono (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study aims to analyze the influence of critical thinking skills and learning interest on students' academic achievement in Surakarta, with ChatGPT serving as a mediating variable. The research employed a quantitative, explanatory survey method. Data were collected from 140 university students who had used ChatGPT in their academic activities, selected through purposive sampling. The research instrument consisted of a questionnaire with a four-point Likert scale that had been tested for validity and reliability. The results revealed that critical thinking skills and learning interest significantly affect academic achievement, both directly and indirectly through ChatGPT's mediating role. The research model demonstrated strong explanatory power with an R² value of 0.719. These findings highlight that integrating artificial intelligence-based technologies, such as ChatGPT, can enhance learning outcomes when combined with the development of critical thinking skills. Therefore, this study emphasizes the importance of implementing adaptive educational strategies that integrate technological use with cognitive skill development to prepare students for the challenges of the digital era.